Packaging Design for E-commerce : Development of a secondary packaging with focus on easy handling and creating a positive unboxing experience - Thorsén, Amanda (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
The e-commerce is an area that has grown considerably in recent years and continues to grow at a rapid pace. It is thereby becoming more and more important for com-panies to distinguish themselves amongst others, not least when it comes to getting customers to return for a second purchase. A good way to do this is to create a posi-tive experience for consumers. As the interaction with the customers has shifted from physical meetings to a computer screen through the spread of online retail, it is im-portant to nourish the few encounters that remain. An important point of interaction is the receiving of purchased goods. The packaging in which the goods are shipped, is thus an important source of communication to the customer, and a perfect means of displaying the company values. This thesis project aims at examining how an optimal packaging for this area can be created, and this was done in collaboration with Arcwise, a SCA business unit, who works with a special type of corrugated cardboard that allows for the production of rounded shaped packages. During the contextual work of this project, where a basic analysis of the market was made, a number of needs could be established. To be able to create a positive user experience and thus a competitive edge in the market, these needs must be fulfilled by packages made for shipping online-bought items. Following these needs, the project’s design phase was carried out with the aim of creating a packaging solution by using the corrugated board developed by Arcwise. This work was done by using creative methods such as brainstorming, workshop and prototyping. To evaluate the ideas, a weighting against criteria was done, and tests were made when the packaging concepts were shipped from Sundsvall to Luleå, to test their durability. Six concepts were narrowed down to a final package, which clearly exhibits the prop-erties of the material. It was designed with the aim for easy folding and packing, and to create a positive unboxing experience for the end customer.